1994
DOI: 10.1021/jm00045a017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Opioid Activity of 7-Oxygenated 2,3,4,4a,5,6,7,7a-octahydro-1H-benzofuro[3,2-e]isoquinolinols

Abstract: 3-(Cyclopropylmethyl)-9-hydroxy-7-oxo-2,3,4,4a alpha,5,6,7,7a alpha- octahydro-1H-benzofuro[3,2-e]isoquinoline (4b) containing the ACNO ring system of morphine and a 7-keto function on ring C has been synthesized and found to possess potent PQW (ED50 = 0.15 mg/kg sc) and anti-Straub tail (ED50 = 0.02 mg/kg sc) activity. As compared to its 7-deoxy analog 1b, introduction of the 7-keto group did not significantly affect binding to any of the three opioid receptors (mu, kappa, and delta), but caused a 34-fold red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…TLC showed a single spot with traces of an unknown impurity at a slightly higher R f . Spectra matched those reported by Weller et al 9 …”
Section: Methodssupporting
confidence: 88%
See 4 more Smart Citations
“…TLC showed a single spot with traces of an unknown impurity at a slightly higher R f . Spectra matched those reported by Weller et al 9 …”
Section: Methodssupporting
confidence: 88%
“…The stereoselective reduction of the trisubstituted alkene 15 was performed with 5% Pt/C rather than the more reactive PtO 2 , while the resulting 85:15 mixture of 4aH,9- O - trans : cis ring juncture isomers 16 were separated by crystallization of the desired trans isomer as a tosylate salt. Weller et al 9 reported a separation of the cis and trans isomers of racemic trans -(±)- 2 with recrystallization from benzene/hexane after subjecting crude 16 to acidic hydrolysis–decarboxylation. Acid hydrolysis led to the desired 4aH,9- O - trans -isoquinolinone 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations